168k views
2 votes
Which equation is modeled below?

2x+(-2)=-2x+6
4x+(-2) = -2x+6
2x+4= 6x+ 2
-2x+4 - 6x+(-2)

Which equation is modeled below? 2x+(-2)=-2x+6 4x+(-2) = -2x+6 2x+4= 6x+ 2 -2x+4 - 6x-example-1
User Lavell
by
5.8k points

2 Answers

1 vote

Answer:

4x + (-2) = -2x + 6

Explanation:

green x represents positive x and red x represents negative

and the same thing for ones but yellow is positive

if i helped can i havae brainllest ❤️

User Leandro
by
5.5k points
0 votes

Answer:

4x + (-2) = -2x + 6

Explanation:

green x represents positive x and red x represents negative

and the same thing for ones but yellow is positive

User Saket Choubey
by
5.9k points